The Effect of Two Bulk Fill Resin Composites on Microleakage in Endodontically Treated Teeth - Tuncer, Safa; Demirci, Mustafa; Tekçe, Neslihan; Tuncer, Aysun Kara; Bag, Harika Gözükara (The Journal of Dentists, 2013)
Purpose: To evaluate the effect of two bulk fill resin composites on microleakage in endodontically treated Class II restorations. Materials and Methods: Twenty-four non-carious molars were selected and randomly divided into three groups (n = 8). The Class II cavity preparations were made with the cervical margin 1 mm below the cementum-enamel junction, and endodontic treatment was performed using a resin-based sealer and gutta-percha points. In Group 1 (Control), resin composite (G-aenial Posterior; GC Corp., Tokyo, Japan) was applied to the interproximal wall, and then restorative material was applied incrementally. In Group 2, resin composite was applied to the interproximal wall, followed by a 4-mm-layer of a bulk fill flowable composite (x-tra base; Voco, GmbH, Cuxhaven, Germany) and the remaining occlusal part of the cavity was filled with resin composite. In Group 3, resin composite was applied to the interproximal wall, followed by a 4mm layer of a bulk fill fiber-reinforced composite (everX Posterior; GC Corp., Tokyo, Japan), and the remaining occlusal part of the cavity was filled with a resin composite. The restorations were then subjected to 500 thermal cycles, each with a dwell time of 20 seconds at 5 and 55 oC. The adaptation at the cervical margin was evaluated by dye penetration, and one tooth was used to evaluate the restorative material interface using SEM. The data were statistically analyzed using the Kruskal Wallis test (p < 0.05). Results: No significant difference in dye penetration was found between the control and the experimental groups. Microleakage was significantly higher on enamel margins compared with the dentin margins for all of the groups. Conclusion: The use of bulk fill restorative materials under resin composites does not affect the sealing ability of restorations.